Development of human health criteria in China for benzo[a]pyrene: A comparison of deterministic and probabilistic approaches. (April 2023) - Yu, Ziling; Xiang, Mingdeng; Ma, Ruixue; Yi, Chuan; Hu, Guocheng; Chen, Xichao; Liu, Yupei; Yu, Yunjiang
Abstract: Human health water quality criteria (HHWQC) for benzo[a]pyrene (BaP) in Chinese rivers and lakes were established using both deterministic and probabilistic approaches. Results showed that the national bioaccumulation factor (BAF) values for BaP at trophic levels 2, 3, and 4 were 342 L/kg, 199 L/kg, and 196 L/kg, respectively. The probabilistic HHWQC for BaP was 0.00407 μg/L for both water and organisms consumption and 0.00488 μg/L for organisms consumption only, which provide a more adequate protection than the deterministic HHWQC. Approximately 32.1% of the studied waters in China exceeded the derived HHWQC, which is likely to have adverse health effects and need be considered more attention. The derived HHWQC for BaP is soly based on Chinese exposure-related activity patterns and field-measured BAFs in surface freshwaters in China, which is important to provide a scientific basis for establishing or revising water quality standards (WQS) and risk management of BaP in water. Graphical abstract: Image 1 Highlights: HHWQC for BaP were developed using both deterministic and probabilistic approaches. Probabilistic HHWQC for BaP is more stringent than deterministic HHWQC. Probabilistic HHWQC for BaP exceeded 32.1% of the Chinese rivers and lakes.